Consumer adoption of electric vehicles in alternative business models. (August 2021) - Huang, Youlin; Qian, Lixian
Abstract: Electric vehicles (EVs) are one of the major green technologies, and existing literature has extensively examined consumer adoption of EVs in an EV-buying business model. By contrast, little attention has been paid to consumers' adoption of EVs in non–ownership-based business models. To fill this literature gap, this study examines the psychological antecedents to, and influencing mechanism for, consumers to adopt EVs in different business models. Using time-lagged design, we show that need for uniqueness (NFU) trait enhances consumers' psychosocial view of EVs. This in turn promotes consumers' intention to adopt EVs in innovative business models such as EV leasing and business-to-consumer EV sharing. We further find that risk aversion negatively affects intention to adopt EVs in innovative business models only. Furthermore, consumers' intention to adopt EVs in innovative business models is positively associated with their intention to buy EVs. Moving beyond the EV-buying business model, we contribute to the sustainable innovation literature by exploring the psychological antecedents to, and mediator of, the psychosocial view in consumers' adoption of EVs in different business models. Our work has significant value for green marketing and public policies of sustainable innovations. Highlights: Need for uniqueness trait has indirect effect on adopting EV-leasing and EV-sharing. Psychosocial view for EVs mediates need for uniqueness trait and EV adoption. Risk averse consumers dislike EV-leasing and EV-sharing but not EV-buying. Intention to adopt EV-leasing and EV-sharing contributes to intention to buy EVs. Policymakers can enhance EV market sustainability via promoting new business models.